Late Holocene landscape evolution of the Gulf of Naples (Italy) inferred from geoarchaeological data. Issue 2 (30th November 2017) - Aucelli, Pietro P.C.; Cinque, Aldo; Mattei, Gaia; Pappone, Gerardo
ABSTRACT: The mapping of landforms in the Gulf of Naples is fundamental to understanding the recent evolution of this perithyrrenian basin controlled by several systems of Quaternary faults and characterised by the presence of the Campi Flegrei and Somma Vesuvius volcanoes. In this paper a 1:85, 000 map of the recent evolution of the Gulf of Naples coasts is presented. This cartographic product has been obtained using a compilation of previously published geoarchaeological coastal studies integrated with new field data. The morphogenetic map suggests a differential evolution of various coastal stretches over the past 2000 years driven not only by measured vertical ground movements and eustatic sea-level rise (of 1 m) but also by eruptions of Mt. Vesuvius, in particular the Plinian eruption of 79 AD and the subsequent reworking of it's products, as well as by the erosive action of the sea.